AN ANALYSIS FIGURATIVE LANGUAGE IN THE SOUND OF SILENCE SONG BY DUO SIMON AND GARFUNKEL - Mukhlasul Fasikh; Ana Peni Batauna (STIBA IEC JAKARTA, 2022)
The purpose of this research is to analyze the Figurative Language and the dominant of figurative found in the sound of Silence Song by Duo Simon and Garfunkel. In this research, the researcher used qualitative data collection methods and data analysis from different sources as the main of this research method. The data is divided into two things such as primary data and secondary data. The technique of collecting data that the researcher used is from journal, article, e-book, credible website. The techniques of analyzing data that the researcher used are reading the song lyrics, identifying the figurative languages, classifying the data coding, interpreting, drawing the conclusion, and writing the report. Based on the result finding, the most figurative language is Oxymoron or Paradox. the song about is inabality of a person to intercat with others and the writers also warn to the listeners the risk of the innabality to communicate. Through this research, people can be helped to understand figurative languages in the songs with the right meaning as well as to encourage to learn English. Keywords: Figurative Language, Song Lyrics, Duo Simon and Garfunkel